Pengaruh Pembiayaan Mudharabah Dan Pembiayaan Musyarakah Terhadap Laba Bersih Bank Umum Syariah Tahun 2014-2017 - Imarotus Suaidah (Jurnal Manajemen dan Inovasi (MANOVA), 2020)
The purpose of the study is to : 1) analyze the effect of mudharabah financing on net income in syariah commercial bank in 2014-2017. 2) analyze the effect of musyarakah financing on net income in syariah commercial bank in 2014-2017. 3) analyze the effect of mudharabah financing and musyarakah financing on net income in syariah commercial bank in 2014-2017. The benefits of this research is 1) this research can provide knowledge on the effect of mudharabah financing and musyarakah financing on net income at syariah commercial banks. 2) can provide an overview for Islamic banking regarding financing that can increase the net income of syariah islamic banks. 3) for investors, this research can be used as consideration in decision making for their investment. This study is quantitative descriptive research. The population in this study are syariah commercial bank in Indonesia which is included in the Indonesian Stock Exchange in 2014-2017. The data analysis technique used is mutiple linear regression analysis which previously carried out analysis prerequisite tests.. The results showed that 1) mudharabah financing has influence on net income in syariah commercial bank in 2014-2017. 2) musyarakah financing has influence on net income in syariah commercial bank in 2014-2017. 3) mudharabah financing and musyarakah financing has influence on net income in syariah commercial bank in 2014-2017